2015
DOI: 10.1158/0008-5472.can-14-2278
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing a Lupus Autoantibody for Targeted Cancer Therapy

Abstract: The specificity of binding by antibodies to target antigens is a compelling advantage to antibody-based cancer therapy, but most antibodies cannot penetrate cells to affect intracellular processes. Select lupus autoantibodies penetrate into cell nuclei, and the potential for application of these antibodies in cancer therapy is an emerging concept. Here, we show that a divalent lupus anti-DNA autoantibody fragment with enhancing mutations that increase its ability to penetrate cell nuclei and bind DNA causes ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(46 citation statements)
references
References 29 publications
(34 reference statements)
1
45
0
Order By: Relevance
“…BRCA2 and PTEN are both known to play roles in DSB repair, and cells deficient in either of these proteins have been reported to have elevated levels of unrepaired DNA damage (4,5,29,35,36). Previous publications have reported that 3E10 is synthetically lethal with BRCA2-deficiency as well as PTEN-deficiency (26,37). Based on this, we elected to assess chemosensitization to Etoposide in BRCA2-deficient PEO-1 cells and PTEN-deficient U251 cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…BRCA2 and PTEN are both known to play roles in DSB repair, and cells deficient in either of these proteins have been reported to have elevated levels of unrepaired DNA damage (4,5,29,35,36). Previous publications have reported that 3E10 is synthetically lethal with BRCA2-deficiency as well as PTEN-deficiency (26,37). Based on this, we elected to assess chemosensitization to Etoposide in BRCA2-deficient PEO-1 cells and PTEN-deficient U251 cells.…”
Section: Resultsmentioning
confidence: 99%
“…This property may further contribute to an increased therapeutic window, further highlighting the clinical potential of this unusual cell-penetrating antibody. Recent work by Noble et al suggests that engineering recombinant 3E10 molecules to comprise multiply valent scFvs can substantially boost activity (37). In this regard, the work presented here not only identifies 3E10 as a novel RAD51 inhibitor but also may help to guide further modifications to the 3E10 scFv to tune its DNA and RAD51 binding properties as a means to further increase efficacy for cancer therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Murine di-scFv with C-terminal Myc and His6 tags was previously designed and evaluated using a combination of in vitro and in vivo studies [9]. Di-scFv lacks an Fc, and therefore efforts to humanize di-scFv focused on VL and VH domains.…”
Section: In Silico Humanization Of Di-scfvmentioning
confidence: 99%
“…Previously a divalent 3E10 single chain variable fragment with improved DNA binding affinity (3E10 (D31N) di-scFv), hereafter referred to as di-scFv was evaluated [9]. Di-scFv lacks the unnecessary 3E10 Fc region that has potential to contribute to non-specific toxicity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation